Exploring the Role of Religious Leaders and Religious Organizations in Combating Corruption in Indonesia - Roshady, Mohammad Ezha Fachriza; Wibowo, Satrio Adjie (Jurnal Sosiologi Reflektif, 2024)
Corruption remains a significant issue in Indonesia, hindering development and governance across various sectors. Despite the strong religious character of Indonesian society, the role of religious leaders in combating corruption has yet to produce substantial results. This study aims to analyze the role and challenges faced by religious leaders in reducing corruption, focusing on their influence in anti-corruption movements at the community level. This research employs a qualitative method with a descriptive approach. Data were collected through literature reviews, interviews, and case studies from religious organizations collaborating with the Corruption Eradication Commission (KPK). Key informants included KPK officials and religious leaders. The findings reveal that while religious leaders possess moral authority and influence within their communities, their involvement in anti-corruption efforts remains limited. The study also identifies several obstacles, such as limited political influence, difficulties in addressing corruption issues, and challenges in effectively communicating anti-corruption messages to the public. Further research is needed to evaluate the long-term effectiveness of religious leaders' involvement and to develop strategies for strengthening their collaboration with state institutions in the fight against corruption. Korupsi tetap menjadi masalah serius di Indonesia yang menghambat perkembangan dan tata kelola di berbagai sektor. Meskipun masyarakat Indonesia dikenal religius, peran pemimpin agama dalam memberantas korupsi belum memberikan dampak yang signifikan. Penelitian ini bertujuan untuk menganalisis peran dan tantangan yang dihadapi pemimpin agama dalam upaya mengurangi korupsi, dengan fokus pada pengaruh mereka terhadap gerakan anti-korupsi di tingkat masyarakat. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Data dikumpulkan melalui tinjauan literatur, wawancara, dan studi kasus dari organisasi keagamaan yang bekerja sama dengan Komisi Pemberantasan Korupsi (KPK). Informan utama mencakup pejabat KPK dan pemimpin organisasi keagamaan. Hasil penelitian menunjukkan bahwa meskipun pemimpin agama memiliki otoritas moral dan pengaruh dalam komunitas mereka, keterlibatan mereka dalam upaya pemberantasan korupsi masih terbatas. Penelitian ini juga mengidentifikasi berbagai hambatan, seperti keterbatasan pengaruh politik, kesulitan dalam memahami isu korupsi, dan tantangan dalam menyampaikan pesan anti-korupsi agar dapat diterima dengan baik oleh masyarakat luas. Penelitian lanjutan diperlukan untuk mengevaluasi efektivitas jangka panjang dari keterlibatan pemimpin agama serta mengembangkan strategi untuk meningkatkan kolaborasi mereka dengan lembaga negara dalam pemberantasan korupsi.